Understanding natural killer cell regulation by mathematical approaches - Watzl, Carsten; Sternberg-Simon, Michal; Urlaub, Doris; Mehr, Ramit (Frontiers in Immunology, 2012)
The activity of Natural Killer (NK) cells is regulated by various processes including education/licensing, priming, integration of positive and negative signals through an array of activating and inhibitory receptors and the development of memory-like functionality. These processes are often very complex due to the large number of different receptors and signaling pathways involved. Understanding these complex mechanisms is therefore a challenge, but is critical for understanding NK cell regulation. Mathematical approaches can facilitate the analysis and understanding of complex systems. Therefore, they may be instrumental for studies in NK cell biology. Here we provide a review of the different mathematical approaches to the analysis of NK cell signal integration, activation, proliferation and the acquisition of inhibitory receptors. These studies show how mathematical methods can aid the analysis of NK cell regulation.